When the guardian becomes the enemy: Targeting ATM in PTEN-deficient cancers. (2nd January 2016) - McCabe, Nuala; Walker, Steven M; Kennedy, Richard D
ABSTRACT: Ataxia telangiectasia mutated (ATM) is an important signaling molecule in the DNA damage response and inhibitors of ATM are under clinical development. We identified a synthetic lethal interaction between ATM inhibition and phosphatase and tensin homolog (PTEN) loss that was the result of increased oxidative stress. Inhibition of ATM therefore represents a novel strategy to target PTEN-associated cancers.